(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was conducted at S A Quadery Teaching Veterinary Hospital (SAQTVH) in Chittagong Veterinary and Animal Sciences University (CVASU), Bangladesh from January, 2014 to June 2014 to conduct about the surgical management of aural hematoma in dog. A total number of 11 dogs were used for surgical management based on history and presenting clinical sings. A history of scratching of right ear since one month ago and swollen abnormal blood filled space under the skin of the ear flap of the dog, no history of external trauma, but intense head-shaking and abrupt increase in the size of the ear flap was noticed by owner of the dog. A thorough examination of the aural canal is carried out under general anesthetic to determine any underlying cause. A fusiform incision made into the skin of the inner pinna with a purse-string suture placed around the incision for closure. To compress the dead space that results from drainage of the hematoma including through and through sutures, or compressing the ear with various materials. The disease was predominant in male (54.54%) than female (45.45%). Local breed were more prone (90.90%) to this disease. The method of operation is considered to be useful as treatment in the field level. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 247-250